RESILIENCE AGAINST BANDITRY AND INSURGENCY IN NIGER STATE, NIGERIA (2015 TO 2022) - Hamza, Kamar; Yusuf, Hauwa'u Evelyn, Professor; Akote, Abubakar Yabagi; Abubakar, Bello Balarabe (UI Scholars Hub, 2022)
The twin evil of banditry and insurgency are threatening the peace of law abiding citizens in rural communities in Niger State, Nigeria. These activities are being noticed from 2015 to 2022. These challenges have made rural dwellers to leave their ancestral home to search for places of abode for the main time. Notwithstanding the people of these communities are still fighting the bandits and insurgents through both government efforts and their own community initiatives. This article investigated the way the communities have suffered in the hands of bandits and insurgents and how they have been confronting them to take control of their communities and continue their lives with the risk of been attacked by these adversaries. The study used both primary and secondary data. The primary data was collection through interview and secondary data was sourced from Daily Trust Newspaper. The qualitative data was analysed in themes. The study concludes that the resilience of the communities has helped them to confront their adversaries, but they need the help of the state to eliminate those threats on a long run.